2002
DOI: 10.1289/ehp.021101213
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic polymorphisms in CYP2E1, MPO, NQO1, GSTM1, and GSTT1 genes with benzene poisoning.

Abstract: Metabolic enzymes involved in benzene activation or detoxification, including NAD(P)H, quinone oxidoreductase 1 (NQO1), cytochrome P450 2E1 (CYP2E1), myeloperoxidase (MPO), glutathione-S-transferase mu-1 (GSTM1), and glutathione-S-transferase theta-1 (GSTT1), were studied for their roles in human susceptibility to benzene poisoning. The potential interactions of these metabolic enzymes with lifestyle factors such as cigarette smoking and alcohol consumption were also explored. We studied 156 benzene-poisoning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 30 publications
5
52
0
9
Order By: Relevance
“…Individuals with variant alleles of rs3813867 and rs2031920 had lower WBC counts, although linear regression showed no apparent association between CYP2E1 polymorphisms and WBC. This finding is consistent with previous studies, 39 reporting that rs3813867 C/C and rs2031920 G/C genotypes tended to be more susceptible to benzene toxicity. Carriers of the heterozygous variant might be associated with an increased risk of acute lymphoblastic leukemia (OR52.8, 95% CI51.2-6.7).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Individuals with variant alleles of rs3813867 and rs2031920 had lower WBC counts, although linear regression showed no apparent association between CYP2E1 polymorphisms and WBC. This finding is consistent with previous studies, 39 reporting that rs3813867 C/C and rs2031920 G/C genotypes tended to be more susceptible to benzene toxicity. Carriers of the heterozygous variant might be associated with an increased risk of acute lymphoblastic leukemia (OR52.8, 95% CI51.2-6.7).…”
Section: Discussionsupporting
confidence: 93%
“…Carriers of the heterozygous variant might be associated with an increased risk of acute lymphoblastic leukemia (OR52.8, 95% CI51.2-6.7). 39 For rs2031920, homozygous variants produced fewer metabolites of PH, E,E-muconic acid (MA), and HQ than homozygous wild types. 40 Our study found similar results; the variant allele of CYP2E1 in the promoter region (rs3813867, rs2031920) had lower levels of WBC counts.…”
Section: Discussionmentioning
confidence: 99%
“…Esse efeito foi observado também em trabalhadores de uma refinaria de petróleo expostos a baixas concentrações de benzeno (0.5 ppm) com aumento na frequência de aneuploidias dos cromossomos 7 e 9 (Kim et al, 2010 (1293 C/C e 1293 G/C) e NQO1 (609 T/T) além da ausência do gene GSTM1 (GSTM1-nulo) tendem a ser mais suscetíveis à toxicidade do benzeno (Wan et al, 2002). Por outro lado, No mesmo dia era aplicado o questionário, adaptado de um estudo caso-controle conduzido na China (Rothman et.…”
Section: Biomarcadores Na Avaliação De Trabalhadores Expostos Ao Benzenounclassified
“…Alguns autores sugerem que nas alterações histológicas da medula óssea há necessidade de pelo menos cinco anos de afastamento da fonte de exposição, para se observar ação reparadora dos danos ocorridos (Wan et al, 2002;Augusto et al, 2005 Os riscos da exposição ao benzeno parecem se estender também aos descendentes biológicos destes trabalhadores (Savitz et al, 1989 No grupo exposto foi informada a ocorrência de quatro abortos espontâneos, todos no primeiro trimestre de gestação, embora essa frequência não tenha sido estatisticamente diferente da observada no grupo controle, onde foram relatados quatro casos de abortos, sendo dois espontâneos e dois induzidos. Aumento na frequência de aborto espontâneo, por exposição paterna ao benzeno, foi relatado na literatura, principalmente em populações da China (Lindbohm et al, 1991).…”
Section: B Cunclassified
See 1 more Smart Citation